2021
DOI: 10.5114/ada.2021.108917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of demodicosis, nailfold capillaroscopy, and oxidative stress in rosacea: a case-control study

Abstract: Introduction Inflammation, immune system disorders, Demodex infestation, neurovascular dysregulation and oxidative stress are thought to be contributory factors in the pathogenesis of rosacea. Aim To evaluate the presence of Demodex mites, the morphologic features of the nailfold capillaries, and the systemic oxidative stress status in patients with rosacea. Material and methods Thirty-one patients diagnosed with rosacea and 37 healthy age- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The predominance of papulopustular type, higher number of patients and longer average disease duration in this study compared with our study may explain the difference in results. Similar to our study, in their study, which included 31 rosacea patients, Karabay et al detected no significant difference in TAS, TOS, and OSI levels between the rosacea and control groups 25 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The predominance of papulopustular type, higher number of patients and longer average disease duration in this study compared with our study may explain the difference in results. Similar to our study, in their study, which included 31 rosacea patients, Karabay et al detected no significant difference in TAS, TOS, and OSI levels between the rosacea and control groups 25 …”
Section: Discussionsupporting
confidence: 90%
“…Similar to our study, in their study, which included 31 rosacea patients, Karabay et al detected no significant difference in TAS, TOS, and OSI levels between the rosacea and control groups. 25 It is thought that there is a strong relationship between rosacea and systemic comorbidities. 26 It was associated with moderate and severe rosacea, hyperlipidemia, hypertension, CVDs, metabolic, and gastrointestinal diseases.…”
Section: Ta B L Ementioning
confidence: 99%
“…The increase in the intensity of Demodex mites has begun to be accepted as an important trigger of the inflammatory cascade and a marker of rosacea. Also, rosacea papulopustules can be treated using acaricides [ 28 , 29 ]. We observed that the density of Demodex mites clearly increased in 80% of patients with rosacea.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there is con icting evidence about the possible anti-in ammatory impact of nicotine on skin conditions, namely, by suppressing neutrophilmediated in ammatory actions (33). It is noteworthy that according to previous studies, it has been well understood that smoking is responsible for causing oxidative stress, leading to the production free radicals and various proin ammatory cytokines in in ammatory skin disease, (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%